Compliance Determinant of Paying Zakat Maal - Tamimah Tamimah (AL-FALAH : Journal of Islamic Economics, 2020)
Purpose: Madura is an island located in East Java which has a community with a high level of religiosity. Sumenep is one of the districts in Madura which has the largest population level among other districts in Madura. However, this is not in line with public compliance in paying zakat maal. Therefore, this study aims to find out whether religiosity, literacy, income, and tax obligation have an effect on community compliance to pay zakat maal.Design/Method/Approach: The data obtained in this study uses primary data obtained from people who pay taxes, using purposive sampling technique by determining people who have reached nisab, and for the analysis, it uses multiple regression.Findings: it shows that only religiosity and tax payment obligations which have an influence, while literacy and income do not have an effect on compliance to pay zakat maal. The implication of this research is as an evaluation for the local government to socialize the important role of the impact of zakat maal on the community, and to increase public understanding of the obligation to pay zakat maal.Originality/Novelty: Lots ofresearchesexamine the obligation to pay zakat fitrah but it is very rare to find research on zakat maal which is an obligation that must also be paid by someone who has assets that have reached Nisab (the minimum amount that a Muslim must have before being obliged to zakat).